Activities of Transport Telematics c - Mikulski, Jerzy; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the proceedings of the 13th International Conference on Transport Systems Telematics, TST 2013, held in Katowice-Ustron, Poland, in October 2013. The 58 papers included in this volume were carefully reviewed and selected for inclusion in this book. They provide an overview of solutions being developed in the field of intelligent transportation systems, and include theoretical and case studies in the countries of conference participants.
Time Dependencies Modelling in Traffic Control Algorithms -- Model of Inference Processes in the Automatic Maritime Communication System -- Microscopic Simulation of the Coordinated Signal Controlled Intersections -- Directions and Benefits of Using Traffic Modelling Software in the Urban Public Transport -- Data Transmission System Architecture for e-Navigation -- Algorithm for Surface Creation from a Cloud of Points.
Keywords: Computer science; Artificial intelligence; Computer simulation; Computer Science; Computers and Society; Information Systems Applications (incl. Internet).; Simulation and Modeling; Artificial Intelligence (incl. Robotics).; Computer Applications